Building the critical anthropology of climate change: Towards a socio-ecological revolution - Baer, Hans A.; Singer, Merrill (London Routledge, 2025)
The book focuses on the critical anthropology of climate change by opening up a dialogue with the two main contending perspectives in the field, namely the cultural ecological and the cultural interpretive perspectives. Guided by these, the authors take a firm stance on the types of changes that are needed to sustain life on Earth as we know it. Within this framework, they explore issues of climate and social equity, the nature of the current era in Earth$1 (Bs geohistory, the perspectives of the elite polluters driving climate change, and the regrettable contributions of anthropologists and other scholars to climate change.s